Penerapan Media Game Snakes and Ladders Terhadap Hasil Belajar Pendidikan Pancasila - Clara Intan; Ani Fiani; Tidi Maharani (STAI AL-AMIN, 2025)
This study aims to determine the completeness of the learning outcomes of Pancasila education students in grade IV of SD Negeri 1 Karang Jaya. This research method is a pseudo-experiment with the design used is one group pre test and post test. The population and sample in this study, namely grade IV of SD Negeri 1 Karang Jaya for the 2024/2025 school year, amounted to 26 students using the saturated sampling method of all populations used as samples. The data collection technique used is a test. The data analysis technique uses Z-Test, with the results of the research for the final test (post test) at a significant level, namely α = 0.05 obtained Zhitung > Ztabel = (11.33 > 1.78) which means that Ho is rejected and Ha is accepted. Thus, the hypothesis proposed in this study is accepted as true. So it can be concluded that the learning outcomes of students after the application of snakes and ladders game media in the learning of Pancasila education for grade IV students of SD Negeri 1 Karang Jaya are significantly complete.